Arrêt sur image : un diocèse du Nordeste brésilien à la veille du Concile - Richard Marin (Caravelle)
July 1, 1957, the murder of the Bishop of Garanhuns (Pernambuco) by one of his priests acts as a dramatic revealing of Church realities of the Brazilian Northeast, five years before Vatican II. This “sacrilegious crime that shocked the world” according to a local daily also expresses the gap between the ultramontane culture of a conscious bishop concerned by reform and that of the clergy’s accommodating Catholicism, very reluctant to go under the yoke of standardization as advocated by Rome. Upstream of drama, the repeated conflicts between the unfortunate bishop and his clergy highlight the failures of Romanization and establish a surprising image of the Church at that time, far from the “Episcopal monarchy” so often mentioned.